Properties of hyoid muscle contraction during tongue lift measurement. (4th December 2019) - Koshi, Naomi; Magara, Jin; Sakai, Shogo; Tsujimura, Takanori; Ono, Kazuhiro; Inoue, Makoto
Abstract: Background: Tongue lift movement (TLM) task is considered a treatment strategy in dysphagic patients. However, there is no evidence of effect of sustained tongue movements on the related muscle contraction. Objectives: The present study aimed to characterise the properties and time‐dependent changes of the electromyographic (EMG) features of suprahyoid muscles during TLM. Methods: Twenty young healthy volunteers were instructed to perform TLM at maximum effort in either the anterior or the posterior position, during measurement of tongue pressure for 7 s. Supra‐ (S‐hyo) and infra‐hyoid (I‐hyo) EMGs were recorded. The area and power frequency of EMG burst and the area under the curve of tongue pressure were compared among the conditions: trials (1st, 2nd vs 3rd trials); anterior vs posterior TLM; and early vs late 3 s of each trial. Results: There was no difference in the tongue pressure among trials or between the early and late 3 s. Anterior tongue pressure was significantly higher than posterior tongue pressure ( P  < .001). The area of I‐hyo EMG burst was significantly larger ( P  = .044), and the power frequency of I‐hyo EMG burst was significantly smaller ( P  = .042) during posterior TLM than anterior TLM. A significant difference in the power frequency of both EMG bursts was observed between early and late stages during both anterior ( P  < .05) and posterior ( P  < .01) TLM. Conclusion: Hyoid muscles may compensate for rapid fatigue of the tongue muscle to maintain tongue pressure by changing their activity pattern during tongue pressure generation.